2020
DOI: 10.30924/mjcmi.25.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The role of benefits in sustaining HRM outcomes

Abstract: Beneficije su oblik indirektnih kompenzacija, koji pokušava postići mnoge ciljeve. Međutim, poduzeća primarno pružaju beneficije, kako bi dokazala da brinu za osobne potrebe zaposlenika, ili žele ponuditi atraktivan i konkurentan ukupni paket kompenzacija. S obzirom da beneficije predstavljaju rastući dio ukupnih troškova kompenzacija te uzevši u obzir da se odnedavno propituje njihov motivacijski potencijal, potrebno je analizirati ulogu beneficija u postizanju primarnih ciljeva upravljanja ljudskim potencija… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…There is a negative association across all age groups, but it is stronger amongst individuals aged 55 years and older) was not confirmed. This contradicts earlier studies that indicated lower absenteeism and turnover rates in organisations providing non-mandatory health and pension insurance (Galeti c and Klind zi c, 2020;O'Brien, 2003;Lee et al, 2006;Daley, 2008). We believe that our results highlight the importance of contextual factors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There is a negative association across all age groups, but it is stronger amongst individuals aged 55 years and older) was not confirmed. This contradicts earlier studies that indicated lower absenteeism and turnover rates in organisations providing non-mandatory health and pension insurance (Galeti c and Klind zi c, 2020;O'Brien, 2003;Lee et al, 2006;Daley, 2008). We believe that our results highlight the importance of contextual factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Regardless of the pandemic, (health)insurance-type benefits were less effective than the former. Researchers (Daley, 2008;de la Torre-Ruiz et al, 2017;Galeti c and Klind zi c, 2020) suggest that cafeteria systems should be considered to increase the efficiency of benefits, where people can choose what they would like the best. The findings of available studies (Rabin, 1994;Vidal-Salazar et al, 2016) show that companies allowing greater freedom to workers in selecting perks and benefits are more successful in their attraction and retention efforts than firms offering fixed benefits systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also value the opportunity to be part of a team, to have a manager who gives constructive feedback, where the work environment is dynamic, fun and allows for constant social interaction. Galetić (2015) reveals that millennials give more importance to non-material rewards and shows that millennials are not necessarily a homogeneous group, recommending that human resource managers should adapt reward strategies to individual characteristics, emphasizing that young millennials with work experience greatly favor job training, teamwork and participation in decision-making.…”
Section: Resultsmentioning
confidence: 99%